2016
DOI: 10.1007/s00418-016-1449-0
|View full text |Cite
|
Sign up to set email alerts
|

GAS1 is present in the cerebrospinal fluid and is expressed in the choroid plexus of the adult rat

Abstract: Growth arrest specific 1 (GAS1) is a GPI-anchored protein that inhibits proliferation when overexpressed in tumors but during development it promotes proliferation and survival of different organs and tissues. This dual ability is caused by its capacity to interact both by inhibiting the signaling induced by the glial cell line-derived neurotrophic factor and by facilitating the activity of the sonic hedgehog pathway. GAS1 is expressed as membrane bound in different organs and as a secreted form by glomerular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 71 publications
(114 reference statements)
0
7
0
Order By: Relevance
“…This is particularly important given that studies in model organisms have sometimes failed to translate to the human condition. GDE2 is the only known GPI anchor-cleaving enzyme in vertebrates that functions at the cell surface in neurons to release GPI-anchored proteins into the extracellular space (26), and GPIanchored proteins can partition to the cerebrospinal fluid (52)(53)(54). Accordingly, determining whether GPI-anchored protein release is impaired in the biofluids of patients with AD could validate the relevance of GDE2 dysfunction to AD and additionally hold promise as diagnostic biomarkers for AD.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly important given that studies in model organisms have sometimes failed to translate to the human condition. GDE2 is the only known GPI anchor-cleaving enzyme in vertebrates that functions at the cell surface in neurons to release GPI-anchored proteins into the extracellular space (26), and GPIanchored proteins can partition to the cerebrospinal fluid (52)(53)(54). Accordingly, determining whether GPI-anchored protein release is impaired in the biofluids of patients with AD could validate the relevance of GDE2 dysfunction to AD and additionally hold promise as diagnostic biomarkers for AD.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we observed two bands for Gas1 in the Western Blot analysis. We had previously reported that there are two isoforms of Gas1 (one of 37 kDa and the other ≈ 34 kDa) [ 49 ]. Perhaps the second band found in the glomerulus is another Gas1 isoform weighing <37 kDa previously described.…”
Section: Discussionmentioning
confidence: 99%
“…This is a very relevant observation since the proximal convoluted tubule is the region of the nephron that performs almost all the reabsorption and secretion of the main solutes in the kidney [ 52 ]. And since there is evidence indicating that Gas1 is secreted by podocytes and/or mesangial cells in the adult [ 12 ] and by perivascular cells in the liver [ 49 ], we believe that more work is necessary in the future to determine the specific cell populations of the nephron that express Gas1 and can also secrete it. We hypothesize that Gas1 may participate in local signaling (autocrine and/or endocrine), as well as paracrine communication and perhaps at as of yet scarcely explored systemic level, since a wide distribution of the soluble form of Gas1 has been found in the body fluids of the rat (cerebrospinal fluid (CSF), blood plasma [ 49 ] and urine [ 12 ]).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations